CARBON STORAGE POTENTIAL IN SEAGRASSES (Enhalus acoroides) IN THE COASTAL WATERS OF JAGO-JAGO VILLAGE CENTRAL TAPANULI REGENCY NORTH SUMATRA - Yenisustri Ani; Syahril Nedi; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in October-November 2014 in the coastal waters of the village of Jago-Jago, Sub Badiri District, Tapanuli of at regency middle of North Sumatera Province. The aims of the study were to determine the carbon content in each section of seagrass and to find out which part of seagrass E. acoroides had the largest carbon storage potential. The method used was a survey method. Analysis of the carbon content in plant parts was done by Walkley and Black method. The results showed the percentage of carbon in plant parts obtained at the highest seagrass leaves from 15,73 to 27,00% and the lowest was at the root of 9,43 to 13,20%. Carbon storage was highest in the leaves ranging from 17,62 to 42,92 gC / m2, and the lowest was at the root, 2,01 to 3,73 gC / m2. Part of seagrass which has the largest carbon storage potential contained in the leaves. To get more information on carbon storage in Village of waters Jago Jago, about the carbon storage potential based on a certain units of time (daily, monthly or annually) in coastal waters Jago-Jago village in helping to tackle climate change.keyword : Enhalus acoroides, Carbon storage, Village of Jago-Jago